Age‐related intrinsic changes in human bone‐marrow‐derived mesenchymal stem cells and their differentiation to osteoblasts - Zhou, Shuanhu; Greenberger, Joel S.; Epperly, Michael W.; Goff, Julie P.; Adler, Carolyn; LeBoff, Meryl S.; Glowacki, Julie (Aging cell, 2008)
Summary In vivo and in vitro studies indicate that a subpopulation of human marrow‐derived stromal cells (MSCs, also known as mesenchymal stem cells) has potential to differentiate into multiple cell types, including osteoblasts. In this study, we tested the hypothesis that there are intrinsic effects of age in human MSCs (17–90 years). We tested the effect of age on senescence‐associated β‐galactosidase, proliferation, apoptosis, p53 pathway genes, and osteoblast differentiation in confluent monolayers by alkaline phosphatase activity and osteoblast gene expression analysis. There were fourfold more human bone MSCs (hMSCs) positive for senescence‐associated β‐galactosidase in samples from older than younger subjects (P < 0.001; n = 17). Doubling time of hMSCs was 1.7‐fold longer in cells from the older than the younger subjects, and was positively correlated with age (P = 0.002; n = 19). Novel age‐related changes were identified. With age, more cells were apoptotic (P = 0.016; n = 10). Further, there were age‐related increases in expression of p53 and its pathway genes, p21 and BAX. Consistent with other experiments, there was a significant age‐related decrease in generation of osteoblasts both in the STRO‐1+ cells (P = 0.047; n = 8) and in adherent MSCs (P < 0.001; n = 10). In sum, there is an age‐dependent decrease in proliferation and osteoblast differentiation, and an increase in senescence‐associated β‐galactosidase‐positive cells and apoptosis in hMSCs. Up‐regulation of the p53 pathway with age may have a critical role in mediating the reduction in both proliferation and osteoblastogenesis of hMSCs. These findings support the view that there are intrinsic alterations in human MSCs with aging that may contribute to the process of skeletal aging in humans.